2017
DOI: 10.3758/s13414-016-1273-6
|View full text |Cite
|
Sign up to set email alerts
|

Low is large: spatial location and pitch interact in voice-based body size estimation

Abstract: The binding of incongruent cues poses a challenge for multimodal perception. Indeed, although taller objects emit sounds from higher elevations, low-pitched sounds are perceptually mapped both to large size and to low elevation. In the present study, we examined how these incongruent vertical spatial cues (up is more) and pitch cues (low is large) to size interact, and whether similar biases influence size perception along the horizontal axis. In Experiment 1, we measured listeners' voice-based judgments of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…About 75% of the explanatory power in height is lost when vocal-tract length is estimated from formant frequencies as opposed to measured in MRI. Even more of this explanatory power is lost when these formants translate into size assessments because of the interaction between fundamental and formant frequencies on size perception (Smith & Patterson, 2005), and other biases in height perception such as the "low is large" heuristic (Pisanski, Isenstein, Montano, O'Connor, & Feinberg, 2017), whereby playing low pitched voices closer to the ground makes them sound larger than when played from higher up in spatial location.…”
Section: Formantsmentioning
confidence: 99%
“…About 75% of the explanatory power in height is lost when vocal-tract length is estimated from formant frequencies as opposed to measured in MRI. Even more of this explanatory power is lost when these formants translate into size assessments because of the interaction between fundamental and formant frequencies on size perception (Smith & Patterson, 2005), and other biases in height perception such as the "low is large" heuristic (Pisanski, Isenstein, Montano, O'Connor, & Feinberg, 2017), whereby playing low pitched voices closer to the ground makes them sound larger than when played from higher up in spatial location.…”
Section: Formantsmentioning
confidence: 99%
“…Structural (or perhaps better said, physiological; Spence and Di Stefano, 2022, on this point), and some statistical correspondences (namely those based on the physical regularities of the environment), such as the pitch-size association, might well be expected to be universal (e.g., Gallace and Spence, 2006;Parise and Spence, 2009; see also Peters et al, 2015;Pisanski et al, 2017). That said, those statistical correspondences that happen to be based on more 'arbitrary' combinations of features (what Walker-Andrews, 1994, has termed 'Arbitrary and Artificial' correspondences), such as, for example, those that have been documented to exist between smell and taste stimuli (e.g., Blank and Mattes, 1990;Spence, 2008), and/or between colour and taste (e.g., Shankar et al, 2010;Spence et al, 2015), or between tastes and visual textures (Barbosa Escobar et al, 2022) are presumably more likely to show robust cultural variation.…”
Section: Semanticmentioning
confidence: 99%
“…As such, choosing sounds that match expectations is crucial to optimizing this information transfer. It has consistently been found that higher pitched sounds tend to be associated with more highly elevated objects, and that lower pitched sounds tend to be associated with lower objects [13,14,15]. This pitch-elevation mapping reflects a statistical regularity of acoustic scenes [16,17].…”
Section: Area Cueing Approachmentioning
confidence: 98%